Crime stories : criminalistic fantasy and the culture of crisis in Weimar Germany - Herzog, Todd (Monographs in German history, 2009)
The Weimar Republic (19181933) was a crucial moment not only in German history but also in the history of both crime fiction and criminal science. This study approaches the period from a unique perspective - investigating the most notorious criminals of the time and the public's reaction to their crimes. The author argues that the development of a new type of crime fiction during this period - which turned literary tradition on its head by focusing on the criminal and abandoning faith in the powers of the rational detective - is intricately related to new ways of understanding criminality amo.